Administrative and Legal Principles of the Activities of the National Police of Ukraine in Preventing and Counteracting Bullying - D. A. Sorochan (Law and Safety)
The negative socio-economic situation and large gaps in the moral and ethical education of the younger generation have led to an increase in the number of cases of deliberate abuse of older and stronger to the smaller and weaker members of educational institutions. The author has studied administrative and legal principles of the activity of the National Police of Ukraine on preventing and counteracting bullying. Based on a comprehensive analysis of national legislation on preventing and combating bullying in Ukraine, the author has determined perspective areas for improving administrative and legal principles in this area. It has been emphasized that the role of the National Police in this area cannot be limited to the preventive registration of a child. It is necessary to develop a set of preventive and educational measures aimed at preventing bullying manifestations among minors. It has been found out that there are no tools to assess the effectiveness of the impact of existing strategies to combat bullying in Ukraine, which necessitates further research in this area. It has been determined that it is necessary to fight not with individual facts of bullying, but to enshrine in the legislation the system of counteraction to harassment in educational institutions, which can be preventive in nature. It has been established that the legislator has introduced a number of amendments over the last few years, which are characterized by the strengthening of the component of protection of children’s rights. A positive novelty is that the main task of the juvenile police was preventive activity instead of punitive one. In general, the regulatory basis for the activities of the National Police of Ukraine to prevent and combat bullying can be divided into two parts: general legislative acts and departmental regulatory acts. It has been noted that the prevention of bullying and the prevention and combating of domestic violence are different aspects of the same problem, which are in constant close cooperation, and then the measures to overcome them should be common.